Is resistance to Covid-19 vaccination a "problem"? A critical policy inquiry of vaccine mandates for healthcare workers - Claudia Chaufan; Natalie Hemsing (AIMS Press, 2024)
As the COVID-19 global vaccination campaign was launched in December of 2020, vaccination became mandatory for many healthcare workers (HCWs) worldwide. Large minorities resisted the policy, and the responses of authorities to this resistance led to damaged professional reputations, job losses, and suspension or termination of practice licenses. The joint effect of dismissals, early retirements, career changes, and vaccine injuries disabling some compliant HCWs from adequate performance has exacerbated existing crises within health systems. Nevertheless, leading health authorities have maintained that the benefits of a fully vaccinated healthcare labor force-believed to be protecting health systems, vulnerable patient populations, and even HCWs themselves-achieved through mandates, if necessary, outweigh its potential harms. Informed by critical policy and discourse traditions, we examine the expert literature on vaccine mandates for HCWs. We find that this literature neglects evidence that contradicts official claims about the safety and effectiveness of COVID-19 vaccines, dismisses the science supporting the contextual nature of microbial virulence, miscalculates patient and system-level harms of vaccination policies, and ignores or legitimizes the coercive elements built into their design. We discuss the implications of our findings for the sustainability of health systems, for patient care, and for the well-being of HCWs, and suggest directions for ethical clinical and policy practice.